NONSTEROID INFLAMMATORY MEDICINES IN PREGNANT WOMEN: THE RISKS OF ADVERSE EVENTS - A.A. Ivanova; A.S. Kolbin (Педиатрическая фармакология, 2011)
The nonsteroidal anti-inflammatory agents are group of medicines, which are used widely in a clinical practice. Pregnant women use these drugs quite often on prescription and in self-treatment. However, data about safety of their using in this patients are limited. Objective was reporting rather more detailed information about safety nonsteroidal anti-inflammatory agents as a group and certain, most common used drugs (acetaminophen, ibuprophen, naproxen, diclofenac, indomethacin, ketoprofen, ketorolac, metamizol, acetylsalicylic acid, celecoxib, meloxicam, nimesulide) during pregnancy. Studies and case reports were founded in electronic databases (reprotox, Medline (at 2011) and handbook C. Schaefer “Drugs during pregnancy and lactation”. Recommendations for prescription this drugs during pregnancy were given.Key words: adverse effect, nonsteroidal anti-inflammatory agents, pregnant women.